A Survey of Effective Factors on Religious Knowledge and Attitudes - gholamreza tajbakhsh; abbas mousavi (توسعه اجتماعی)
The study aimed to investigate the factors influencing knowledge and attitudes of religious high school students of Susangerd city. Survey research, and enjoying the simple random sampling method, and the content is valid and reliable questionnaire-made. The population of all high school students in the academic year 2013-2014 Susangerd and sample size is 290. Results show that, among the religious aspects, average 89/15 bit later than others, emotional, behavioral and mental and 13/19, respectively, with an average of 11/78 in the next priority. Also, the results showed that the Pearson correlation coefficient between the religious use of the media, participation in religious ceremonies, family income, family, friends, students of religion, caste and religious attitude and there is a significant positive relationship. However, a significant inverse relationship between educations level of parents and religious attitude there. Nonetheless, there is no significant relationship between the level of family and religious attitudes. ANOVA showed that between religious attitudes based on the type of communication there is.